Sensitive liberals and unfeeling conservatives? Interoceptive sensitivity predicts political liberalism. (2022) - Ruisch, Benjamin C.; Von Mohr, Mariana; Naber, Marnix; Tsakiris, Manos; Fazio, Russell H.; Scheepers, Daan T.
Abstract: The stark divide between the political right and left is rooted in conflicting beliefs, values, and personality—and, recent research suggests, perhaps even lower-level physiological differences between individuals. In this registered report, we investigated a novel domain of ideological differences in physiological processes: interoceptive sensitivity—that is, a person's attunement to their own internal bodily states and signals (e.g., physiological arousal, pain, and respiration). We conducted two studies testing the hypothesis that greater interoceptive sensitivity would be associated with greater conservatism: one laboratory study in the Netherlands using a physiological heartbeat detection task and one large-scale online study in the United States employing an innovative webcam-based measure of interoceptive sensitivity. Contrary to our predictions, we found evidence that interoceptive sensitivity may instead predict greater political liberalism (versus conservatism), although this association was primarily limited to the American sample. We discuss implications for our understanding of the physiological underpinnings of political ideology.